2013
DOI: 10.1038/ejhg.2013.281
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1/2 mutations and FMR1 alleles are randomly distributed: a case control study

Abstract: BRCA mutation carriers were reported to display a skewed distribution of FMR1 genotypes, predominantly within the low normal range (CGG repeat number o26). This observation led to the interpretation that BRCA1/2 mutations are embryo-lethal, unless rescued by 'low FMR1 alleles'. We undertook to re-explore the distribution of FMR1 alleles subdivided into low, normal and high (o26, 26-34, and 434 CGG repeats, respectively) subgenotypes, on a cohort of 125 Ashkenazi women, carriers of a BRCA1/2 founder mutation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
3
8
1
Order By: Relevance
“…These FMR1 CGG allele distribution differences results are in line with those of Weghofer et al (2012) who previously reported a unique FMR1 CGG allele distribution in BRCA1/BRCA2 mutation carriers undergoing fertility treatment compared with noncarriers recruited from an infertility clinic. In line with our previous data, smaller studies published from Israel (Dagan et al, 2014), Italy (Ricci et al, 2014) and Holland (Brandão et al, 2013) also failed to show the lack of long CGG FMR1 alleles in BRCA mutation carriers. The basic premise of the Weghofer et al (2012) study was that the long CGG allele in the presence of a BRCA mutation may be embryonic lethal, and that rescue may be conferred by the existence of short (<26 repeats) alleles; however, our results do not support this notion.…”
Section: Discussionsupporting
confidence: 90%
“…These FMR1 CGG allele distribution differences results are in line with those of Weghofer et al (2012) who previously reported a unique FMR1 CGG allele distribution in BRCA1/BRCA2 mutation carriers undergoing fertility treatment compared with noncarriers recruited from an infertility clinic. In line with our previous data, smaller studies published from Israel (Dagan et al, 2014), Italy (Ricci et al, 2014) and Holland (Brandão et al, 2013) also failed to show the lack of long CGG FMR1 alleles in BRCA mutation carriers. The basic premise of the Weghofer et al (2012) study was that the long CGG allele in the presence of a BRCA mutation may be embryonic lethal, and that rescue may be conferred by the existence of short (<26 repeats) alleles; however, our results do not support this notion.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, a similar result was reported in the Israeli study [13], where BRCA1 /2 mutation carriers, a large majority of them already diagnosed with breast cancer, demonstrated only in 24.8% low FMR1 alleles, while random controls demonstrated low FMR1 alleles in 31.5% of women.…”
Section: Discussionsupporting
confidence: 83%
“…Instead, a direct impact of low CGG repeats on these outcomes cannot be ruled out. On the other hand, as proposed by some authors, a low number of CGG repeats supposedly rescued embryos with BRCA1/2 mutation [42,105], even though this association has been refuted by others [10,21].…”
Section: Fmr1 Gene Mutations and Reproductive Agingmentioning
confidence: 91%